التمويل الإسلامي في أفريقيا: الفرص والتحديات "دول الشمال الأفريقي نموذجا": Islamic Finance in Africa: Challenges and Opportunities: (North African Countries as a model) - فضل عبد الكريم البشير (Journal of North African Economies, 2025)
North African countries are the leading incubators of Islamic finance, despite their humble enlargement and the decline of this industry in many countries. This study aims to track and assess the situation of the Islamic finance industry in this region of the globe to identify the declining reasons, by focusing on the reality of Islamic finance origins and evolution, the considering available opportunities and the challenges that increase the need for rethinking in the existing experience of the Islamic financial industry in some of those countries. which include Islamic banks, Islamic Sukuk, and Takaful insurance, In terms of size, status, opportunities, and challenges. The study provided a situation assessment and concluded that many opportunities are available for Islamic finance in those countries as well as challenges of the legislation Acts, and governing laws. and recommended further investigation of the declining reasons.